High-Fat Diet-Induced Obesity Model Does Not Promote Endothelial Dysfunction via Increasing Leptin/Akt/eNOS Signaling - Rocha, Vanessa da Silva; Claudio, Erick Roberto Gonçalves; da Silva, Vitor Loureiro; Cordeiro, Jóctan Pimentel; Domingos, Lucas Furtado; da Cunha, Márcia Regina Holanda; Mauad, Helder; Nascimento, Thiago Bruder do; Lima-Leopoldo, Ana Paula; Leopoldo, André Soares (Frontiers in Physiology, 2019)
Experimental studies show that the unsaturated high-fat diet-induced obesity promotes vascular alterations characterized by improving the endothelial L-arginine/Nitric Oxide (NO) pathway. Leptin seems to be involved in this process, promoting vasodilation via increasing NO bioavailability. The aim of this study was to test the hypothesis that unsaturated high-fat diet-induced obesity does not generate endothelial dysfunction via increasing the vascular leptin/Akt/eNOS signaling. Thirty-day-old male Wistar rats were randomized into two groups: control (C) and obese (Ob). Group C was fed a standard diet, while group Ob was fed an unsaturated high-fat diet for 27 weeks. Adiposity, hormonal and biochemical parameters, and systolic blood pressure were observed. Concentration response curves were performed for leptin or acetylcholine in the presence or absence of Akt and NOS inhibitor. Our results showed that an unsaturated high-fat diet promoted a greater feed efficiency (FE), elevation of body weight and body fat (BF), and an adiposity index, characterizing a model of obesity. However, comorbidities frequently associated with experimental obesity were not visualized, such as glucose intolerance, dyslipidemia and hypertension. The evaluation of the endothelium-dependent relaxation with acetylcholine showed no differences between the C and Ob rats. After NOS inhibition, the response was completely abolished in the Ob group, but not in the C group. Furthermore, Akt inhibition completely blunted vascular relaxation in the C group, but not in the Ob group, which was more sensitive to leptin-induced vascular relaxation. L-NAME incubation abolished the relaxation in both groups at the same level. Although Akt inhibitor pre-incubation reduced the leptin response, group C was more sensitive to its effect. In conclusion, the high-unsaturated fat diet-induced obesity improved the vascular reactivity to leptin and does not generate endothelial dysfunction, possibly by the increase in the vascular sensitivity to leptin and increasing NO bioavailability. Moreover, our results suggest that the increase in NO production occurs through the increase in NOS activation by leptin and is partially mediated by the Akt pathway.